Ultra-low-carbon hot-rolled steel plate with excellent enameling performance and manufacturing method of ultra-low-carbon hot-rolled steel plate
By designing appropriate chemical components and microstructures in ultra-low-carbon hot-rolled steel plates to form composite inclusions of manganese sulfide and ferrous sulfide, the problem of poor enamel coating performance in the electrostatic enamel process is solved, and excellent anti-scale explosion, tightening, anti-bubble, pinhole and other properties are achieved, reducing production costs.
Patent Information
- Application Number
- CN202311154922.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing low-carbon or ultra-low-carbon and high-oxygen enamel steel plates are difficult to achieve excellent enamel coating performance in electrostatic enamel technology, especially in terms of resistance to scale explosion, adhesiveness, and resistance to bubbles, pinholes and black spots.
Ultra-low-carbon hot-rolled steel plates with weight percentages of chemical components of C: 0.001 to 0.008%, Si≤0.05%, Mn: 0.1 to 1.0%, etc. are used, and microstructures of ferrite + a small amount of cementite are formed through smelting, refining, continuous casting, hot rolling and coiling, as well as composite inclusions of manganese sulfide and ferrous sulfide to ensure that the inclusion mass percentage content is above 0.13%.
The good plasticity and enamel coating properties of the steel plate are achieved, and the requirements of the electrostatic enamel process to resist scale explosion, tightness and bubble resistance, pinholes and black spots, and at the same time, the cost of alloy and process manufacturing costs are reduced.
Smart Images

Figure CN119592870A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of enameled steel plate processing, and particularly relates to an ultra-low carbon hot-rolled steel plate with excellent enameling performance and a manufacturing method thereof. Background Art
[0002] When manufacturing enameled baking trays, flat plates and water heater inner tanks, the steel plate is processed and formed, welded and surface treated such as sandblasting and degreasing, and then enameled and sintered once. In the past, the wet enameling process was mainly used. With the wet enameling process, the adhesion and anti-scale matching of the enamel and steel plate are relatively good, but the porcelain layer is thick and uneven, the surface quality cannot be guaranteed, and the enamel production efficiency is low. The electrostatic enameling process replaces the traditional wet enameling process. The thickness of the porcelain layer is easy to control, and a thinner and more uniform porcelain layer can be obtained. The porcelain layer is denser, the appearance is more beautiful, and the production efficiency is high. Therefore, the electrostatic enameling process is increasingly used in the processing of enameled products such as enameled baking trays, flat plates and water heater inner tanks.
[0003] The electrostatic enamel process also places higher requirements on the enameling performance of steel plates. When ordinary enameled steel plates are used in the electrostatic enamel process, the bonding force between the enamel powder and the steel plate, that is, the adhesion, is not as good as wet enamel. In addition, the electrostatic enamel layer is dense and has poor air permeability, which makes it more likely to produce scale explosion, bubbles, pinholes, black spots and other defects, which will seriously damage the intrinsic quality and appearance quality of enameled products. Especially when only one glaze is applied, the steel plate has higher requirements in terms of anti-scale explosion, adhesion, and resistance to defects such as black spots, bubbles, pinholes, etc.
[0004] Among the existing enameled steels, ultra-low carbon high-oxygen steel is the most commonly used enameled steel. The high oxygen content mainly forms oxides in the steel as hydrogen storage traps. The purpose of controlling ultra-low carbon is mainly to reduce enamel defects such as enamel bubbles and pinholes and improve the plasticity of the steel.
[0005] Chinese patent application No. 200780034772.5 discloses "enamel glazing processed products and enamel processed products". The steel has given control ranges for elements such as C, Si, Mn, P, S, and O, and precious elements such as Ti and Co are added. The steel involves many types of alloy elements and a wide range of contents. An oxide film formed by the oxides of the steel plate components is formed on the surface of the steel plate to improve the adhesion between the enamel layer and the steel plate. The steel plate needs to undergo multiple processes such as hot rolling, cold rolling, annealing and tempering rolling.
[0006] Chinese patent application No. 201810663362.7 discloses "a low-cost high-oxygen enameled steel produced by CSP process and its manufacturing method", which is also a high-oxygen steel, with low C and Mn content, and no need to add expensive alloying elements such as Nb, Ti, and V. It adopts CSP thin slab continuous casting and rolling process, and the finishing rolling temperature is controlled in a narrow temperature range of 880±20℃. It relies on the MnO and MnS inclusions formed in the steel as hydrogen storage traps, and the metallographic structure is recrystallized ferrite + pearlite + a small amount of deformation structure. The steel plate produced has good phosphorus explosion resistance and mechanical properties. However, pearlite in steel is prone to produce defects such as enamel bubbles and pinholes during enameling, and the lower limit of the content of some key elements such as oxygen and sulfur is not limited in the steel plate composition.
[0007] Chinese patent application No. 201710064842.7 discloses "a hot-rolled enameled steel plate for subway decoration and its manufacturing method". The chemical composition mass percentage of the steel plate is: C 0.05-0.09%, Si 0.10-0.20%, Mn 0.65-0.95%, P≤0.012%, S≤0.015%, Ti 0.05-0.10%, Als 0.015-0.045%, Cr 0.10-0.20%, and the rest is iron and unavoidable impurities. Although the yield strength of the steel plate reaches more than 390MPa, due to the high carbon content in the steel, ferrite + a small amount of cementite is formed, and the grain size is above level 10, which is not conducive to improving the steel plate's anti-bubble, pinhole or black spot enameling performance.
[0008] In summary, it is difficult for existing low-carbon or ultra-low-carbon, high-oxygen enameled steels to achieve excellent plasticity while also having good resistance to scale explosion, adhesion, and resistance to black spots, bubbles, pinholes, etc., so as to meet the requirements of using the electrostatic enameling process to prepare enameled baking trays, flat plates, water heater tanks and other enameled products without defects such as scale explosion, bubbles, pinholes and black spots. Summary of the invention
[0009] The object of the present invention is to provide an ultra-low carbon hot-rolled steel plate with excellent enameling performance and a method for manufacturing the same. The obtained steel plate has good plasticity and enameling performance, and meets the requirements of the electrostatic enameling process for resistance to scale explosion, adhesion, and resistance to defects such as bubbles, pinholes and black spots; moreover, the hot rolling process allows a wider heating temperature, rolling process and cooling process, the process is easier to implement and stably control, the production rhythm is fast, and the process manufacturing cost is low.
[0010] To achieve the above object, the technical solution of the present invention is:
[0011] An ultra-low carbon hot-rolled steel plate with excellent enameling performance, the chemical composition weight percentage of which is: C: 0.001-0.008%, Si≤0.05%, Mn: 0.1-1.0%, P≤0.035%, S: 0.015-0.050%, Al≤0.010%, N≤0.005%, O: 0.025-0.055%, Cu: 0.01-0.10%, Cr: 0.01-0.10%, Ni≤0.05%, Mo≤0.05%, the balance includes Fe and unavoidable impurity elements; and it is also necessary to simultaneously meet the following requirements:
[0012] Mn / [(55 / 32)×S+(55 / 16)×O]≥0.6.
[0013] Furthermore, the balance is Fe and other inevitable impurities.
[0014] Furthermore, the chemical composition weight percentage of the steel plate also includes one or two of Nb: 0.0005-0.045% and B: 0.0003-0.003%.
[0015] Furthermore, the chemical composition of the steel plate also satisfies: 0.02%≤Cu+Cr+Ni+Mo≤0.20%.
[0016] Preferably, the chemical composition of the steel plate also satisfies: Mn / [(55 / 32)×S+(55 / 16)×O]≥1.
[0017] The microstructure of the steel plate of the present invention is ferrite + a small amount of cementite; the ferrite grain size level is 7-10, and manganese oxysulfide and ferrous sulfide composite inclusions are dispersed on the ferrite, and the mass percentage of the inclusions is above 0.13%.
[0018] The steel plate of the present invention has a yield strength of ≥180MPa, a tensile strength of ≥280MPa, and an elongation of ≥38%.
[0019] In the chemical composition design of the ultra-low carbon hot-rolled steel plate with excellent enameling performance described in the present invention:
[0020] Carbon: Carbon exists in the form of solid solution, cementite and metal compound precipitation phase such as niobium carbide, boron carbide, etc. It is a key element to improve the yield strength and tensile strength of steel plates. The higher the carbon content, the more carbides or solid solution carbon precipitates, and the higher the strength. However, the carbon content also significantly damages the plasticity and formability. The carbon content of the present invention is controlled at 0.001-0.008%, which not only ensures the precipitation of carbides such as niobium carbide, niobium carbonitride or boron carbide and a small amount of cementite, but also the presence of solid solution carbon, so as to achieve a good match between strength and plasticity. Because the amount of carbon in the form of solid solution and cementite has a key influence on the surface quality of enamel, mainly because carbon will generate gases such as carbon monoxide during the enamel firing process, which is the main source of enamel bubbles, pinholes and black spots, etc. Therefore, the present invention controls the carbon content to not be higher than 0.008%.
[0021] Aluminum: Aluminum is a strong deoxidizing element. If the aluminum content is high, the oxygen content will decrease, and the formed aluminum oxide inclusions will have poor plasticity, which will damage the processability of the steel and also damage the adhesion of the enamel. Therefore, the lower the aluminum content, the better. Therefore, the present invention controls the aluminum content to ≤0.010%.
[0022] Silicon: Silicon is a harmful element. A high silicon content is not conducive to the adhesion between the steel plate and the enamel during enameling, which damages the enameling performance. In addition, silicon is very easy to form oxide inclusions with poor ductility, which damages the plasticity of the steel. Therefore, the silicon content is controlled to ≤ 0.05% in the present invention.
[0023] Manganese: Manganese reacts with oxygen to form manganese oxide, and also reacts with sulfur to form manganese sulfide. In the present invention, by matching appropriate amounts of oxygen, manganese and sulfur, composite inclusions such as manganese oxysulfide and ferrous sulfide are mainly formed in the steel. When Mn / [(55 / 32)×S+(55 / 16)×O]≥1, composite inclusions mainly composed of manganese oxysulfide are formed; when 0.6≤Mn / [(55 / 32)×S+(55 / 16)×O]<1, composite inclusions such as manganese oxysulfide and ferrous sulfide are formed. These inclusions will be generated in the molten steel, and their quantity, form and distribution in the steel are relatively fixed, and are rarely affected by heating, rolling, cooling and temperature. They are stable hydrogen storage traps. The presence of inclusions is beneficial to improving the anti-scale explosion. The amount of manganese added is Mn / [(55 / 32)×S+(55 / 16)×O]≥0.6, preferably, Mn / [(55 / 32)×S+(55 / 16)×O]≥1. However, a large number of inclusions or large-particle inclusions will severely damage the plasticity and formability of the steel. Manganese is an effective element for improving strength, but if the manganese content is too high, the adhesion of the enamel will deteriorate after pickling, and defects such as bubbles and black spots will easily occur. Therefore, the manganese content of the present invention is controlled at 0.1-1.0%.
[0024] Sulfur: When adding an appropriate amount of sulfur, when the oxygen content in the steel is also high, sulfur, oxygen and manganese are more likely to form manganese oxysulfide composite inclusions, and sulfur may also form ferrous sulfide inclusions, and MnS, FeS, MnO, etc. mainly exist in the form of composite inclusions, which can not only significantly improve the long strip shape of pure MnS after rolling, reduce the damage to the transverse plasticity of the steel plate, but also avoid the formation of a single coarse particle inclusion. However, when the sulfur content is too high, such as higher than 0.050%, the inclusion content in the steel is too high, and the plasticity of the steel plate is difficult to ensure. Therefore, the sulfur content of the present invention is controlled at 0.015-0.050%.
[0025] Oxygen: Oxygen is a decarburizing element during the smelting process. A higher oxygen content is beneficial to decarburization. Oxygen in steel forms oxide inclusions, which are beneficial hydrogen storage traps and improve the anti-scale explosion performance of the steel plate. It can form manganese oxide inclusions with manganese. At a higher sulfur content, it forms manganese oxide sulfide inclusions or inclusions composed of manganese oxide and ferrous sulfide. The type and amount of inclusions formed depend on the content of oxygen, manganese and sulfur in the steel and the chemical ratio between them. When the oxygen content is lower than 0.025%, the amount of inclusions formed is small, which is not enough to ensure the anti-scale explosion performance of the steel plate. On the contrary, when the oxygen content is higher than 0.055%, not only the number of inclusions is large but also the particle size is large, which will seriously damage the plasticity of the steel plate. Therefore, the oxygen content of the present invention is controlled at 0.025-0.055%.
[0026] Phosphorus: Phosphorus is easily segregated on the grain boundaries in steel, and is likely to generate bubbles and black spots during enameling, which damages the surface quality of the enamel. The lower the phosphorus content in steel, the better. Therefore, the present invention controls the phosphorus content to ≤0.035%.
[0027] Nitrogen: Nitrogen, like carbon, can exist as a solid solution element and can also form compounds with alloy elements such as niobium. Nitrogen compounds can not only strengthen the matrix, but also serve as a hydrogen storage trap to improve the anti-scale explosion performance. However, nitrogen existing in the form of solid solution is prone to cause aging of the steel plate, that is, if it is left for too long, the yield strength of the steel plate will increase and the plasticity will decrease. If the nitrogen content is too high, the amount of nitride formed will also be high, which will also damage the plasticity of the steel. Therefore, the present invention controls the nitrogen content to ≤0.005%.
[0028] Furthermore, when niobium and boron are added, carbides, nitrides or carbonitrides of niobium and boron can be formed, which is a beneficial supplement for further improving the hydrogen storage performance and anti-scale explosion performance of steel.
[0029] Boron: Boron can form compounds with carbon and nitrogen, or be dissolved in steel, and can serve as a hydrogen storage trap. Adding an appropriate amount of boron to hot-rolled plates is beneficial to improving the anti-scale explosion performance of steel plates. If the boron content is too high, cracks are easily generated on the ingot during the continuous casting process. Therefore, the boron content of the present invention is controlled at 0.0003-0.003%.
[0030] Niobium: Niobium has a solid solution strengthening effect. Niobium is also a strong carbon and nitride forming element. The dispersed precipitate phase formed can not only improve the strength of the steel plate, but also is a good hydrogen storage trap, improving the scale resistance. Niobium is a precious metal, and the addition amount will significantly increase the cost. Therefore, the niobium content of the present invention is controlled at 0.0005-0.045%.
[0031] Copper, chromium, nickel and molybdenum: The steel contains an appropriate amount of copper, chromium, nickel and molybdenum to accelerate the adhesion reaction during the enameling process. Copper, chromium, nickel and molybdenum will also affect the pickling speed of the steel plate. When the content is too high, the pickling speed will be inhibited and the pickling effect will be affected. However, these alloy elements are precious metals, and the addition amount will significantly increase the alloy cost. Therefore, in the present invention, copper is controlled to be 0.01-0.10%, chromium is 0.01-0.10%, nickel is ≤0.05%, and molybdenum is ≤0.05%; preferably, the total content of copper, chromium, nickel and molybdenum satisfies: 0.02% ≤ Cu+Cr+Ni+Mo ≤0.20%.
[0032] The present invention also provides a method for manufacturing an ultra-low carbon hot-rolled steel plate with excellent enameling performance, comprising the following steps:
[0033] 1) Smelting, refining and continuous casting
[0034] Smelting, RH or LF refining, and continuous casting into slabs according to the above composition;
[0035] 2) Hot rolling
[0036] Slab heating temperature: 1100-1250℃, followed by hot rolling, including rough rolling and finish rolling, and the final rolling temperature is controlled at 800-960℃;
[0037] 3) Coiling
[0038] The hot-rolled steel plate is cooled by air or water and then coiled at a coiling temperature of 520 to 800°C.
[0039] In the manufacturing method of the steel plate of the present invention:
[0040] Converter blowing and refining ensure that the basic composition of the molten steel meets the design requirements of the present invention, decarburize and remove harmful gases and other harmful elements in the steel, add necessary alloy elements, and adjust the composition. In particular, it is necessary to control the elements such as carbon, nitrogen, sulfur and oxygen, and add appropriate amounts of manganese, copper, chromium, nickel, molybdenum, niobium, boron and other alloy elements.
[0041] Continuous casting: The smelted molten steel is continuously cast into slabs. During the casting process, carbon and nitrogen addition must be prevented. Carbon-free protective slag can be used, and vacuum or inert gas protection casting can be used to prevent air from entering.
[0042] Hot rolling: The slab is heated for hot rolling, and the heating temperature is controlled at 1100-1250°C so that the slab is transformed into austenite structure and fully homogenized during the heating process.
[0043] In addition, the present invention adopts an ultra-low carbon component design, the hot rolling final rolling temperature is controlled at 800-960°C, and the coiling temperature is controlled at 520-800°C. In a wide rolling and coiling temperature range, hot rolling can be completed in the austenite region (not higher than 960°C) or in the ferrite region (not lower than 800°C). As long as the final rolling temperature is not lower than 800°C, the rolling can be completed to ensure the completion of ferrite recrystallization and grain growth. The microstructure of the steel plate is composed of ferrite + a small amount of cementite, and the ferrite grain size is controlled between 7 and 10 levels, which can obtain a better match between plasticity and yield strength.
[0044] The inclusions in the steel can stably maintain their precipitation form and quantity during the slab heating and rolling process, and are difficult to dissolve even after long-term heating at high temperature before hot rolling. Therefore, the inclusions have stability in form, size and quantity, which well guarantees the hydrogen storage performance and anti-scale explosion performance of the steel.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The present invention adopts ultra-low carbon, adds a very small amount of alloy elements such as copper, chromium, nickel, molybdenum, niobium or boron, and controls the content of elements such as Si, P, Al, N and the like within a relatively low range as much as possible to meet the plasticity requirements of the steel plate. Combined with the control of the content of oxygen, sulfur and manganese, a composite inclusion composed of manganese oxysulfide and ferrous sulfide is formed, and the mass percentage of the inclusions formed in the steel is ensured to be above 0.13%. These inclusions are beneficial hydrogen storage traps, and rely on the formation of sufficient inclusions in the steel to ensure that the steel plate has excellent anti-scale explosion performance. The formation of composite inclusions can significantly improve the shape of the simple MnS inclusions in the form of long strips after rolling, reduce the damage to the transverse plasticity of the steel plate, and at the same time, it can also avoid the formation of large particles and aggregated inclusions, which is very beneficial for stabilizing and improving the anti-scale explosion performance of the hot-rolled steel plate. In addition, the amount of precious elements added to the steel plate is as small as possible, and the alloy cost is also relatively low.
[0047] The present invention, based on the composition design, combines the process control of heating and rolling temperature to ensure that the microstructure of the steel plate consists of ferrite + a small amount of cementite, the ferrite grain size is controlled between 7 and 10 levels, no large or large amount of cementite or pearlite is formed, the plasticity of the steel plate is improved, and the generation of surface defects such as bubbles, pinholes and black spots caused by the escape of CO gas during the enameling process is avoided.
[0048] In the manufacturing method of the present invention, due to the ultra-low carbon component design, hot rolling can be completed in both the austenite region and the ferrite region, both of which can ensure ferrite recrystallization and grain growth, and each process is easy to implement and stably controlled. The traditional hot rolling process needs to complete the rolling within the austenite temperature range and use laminar cooling. Compared with the cold rolling manufacturing process, the process is short and the production rhythm is fast.
[0049] The steel plate of the present invention has a yield strength of ≥180MPa, a tensile strength of ≥280MPa, and an elongation of ≥38%, achieving a good match between the mechanical properties and the enameling properties of the steel plate. The steel plate is not only suitable for wet enameling and electrostatic enameling with one-time enameling and one-time firing, but can also be used for two-time enameling and two-time firing or two-time spraying and one-time firing. The steel plate has good machinability and enameling properties in the production of water heater inner tanks, baking trays, flat plates, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a microstructure photograph of the steel plate of Example 1 of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described below by way of embodiments and drawings, but this is not intended to limit the present invention. Those skilled in the art may make modifications or improvements based on the basic idea of the invention, but as long as they do not deviate from the basic idea of the invention, they are all within the scope of the present invention.
[0052] The composition and process parameters of the embodiments of the present invention are shown in Table 1 and Table 2, wherein the balance of the composition includes Fe and unavoidable impurities.
[0053] The performance tests were performed on the samples obtained in Examples 1-10 of the present invention, and the test results are listed in Table 3.
[0054] Mechanical properties: Steel plates were cut transversely and processed into tensile specimens according to GB / T 2975. The parallel part of the specimen had a width of 20 mm and a gauge length of 80 mm. The tensile test method was in accordance with GB / T 228.1.
[0055] Enameling performance: Cut samples of about 200×200mm for enameling test. The specific enameling test steps include: the sample surface is degreased after pickling or sandblasting, then washed, dried, and electrostatic dry powder sprayed. The firing temperature is 840℃±10℃, the holding time is 4min, and the thickness of the obtained porcelain layer is 150μm±30μm. After the enameling test, the sample is placed in the atmosphere for 48 hours and the surface of the sample is observed with the naked eye for defects such as scale explosion, pinholes, bubbles and black spots. The drop weight test is carried out according to the standard EN 10209:2013 Appendix C to test the adhesion level, where A1 represents the best adhesion level.
[0056] like Figure 1As shown, the microstructure of the hot-rolled steel plate obtained by the present invention consists of ferrite + a small amount of cementite, the ferrite grain size is controlled between 7 and 10 levels, manganese oxysulfide and ferrous sulfide composite inclusions are dispersed on the ferrite, and the mass percentage of the inclusions is above 0.13%.
[0057] As can be seen from Table 3, the yield strength of the hot-rolled steel sheet obtained by the present invention is not less than 180MPa, the tensile strength is not less than 280MPa, and the elongation is not less than 38%. The electrostatic spraying process conditions are adopted, no scale explosion phenomenon occurs, the adhesion performance is excellent, and the porcelain layer has excellent anti-pinhole, bubble and black spot performance when the thickness is 150μm±30μm.
[0058] In summary, the hot-rolled steel plate with excellent enameling performance described in the present invention can solve the problems of anti-scale, anti-adhesion and anti-pinhole defects that ordinary low-carbon steel plates cannot meet in the electrostatic enameling process, and is widely applicable and has good application prospects.
[0059] It should be noted that the embodiments listed above are only specific embodiments of the present invention. Within the protection scope of the present invention, similar changes or modifications made can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and should all fall within the protection scope of the present invention.
[0060]
[0061]
[0062]
Claims
1. An ultra-low carbon hot-rolled steel plate with excellent enameling performance, the chemical composition weight percentage of which is: C: 0.001-0.008%, Si≤0.05%, Mn: 0.1-1.0%, P≤0.035%, S: 0.015-0.050%, Al≤0.010%, N≤0.005%, O: 0.025-0.055%, Cu: 0.01-0.10%, Cr: 0.01-0.10%, Ni≤0.05%, Mo≤0.05%, the balance includes iron and other unavoidable impurities; and it is also necessary to meet the following requirements at the same time: Mn / [(55 / 32) × S+(55 / 16) × O]≥0.6。 2. The ultra-low carbon hot-rolled steel sheet with excellent enameling performance according to claim 1, characterized in that: The balance is Fe and other inevitable impurities.
3. The ultra-low carbon hot-rolled steel sheet with excellent enameling performance according to claim 1 or 2, characterized in that: The chemical composition weight percentage also includes one or two of Nb: 0.0005-0.045% and B: 0.0003-0.003%.
4. The ultra-low carbon hot-rolled steel sheet with excellent enameling performance as claimed in claim 1, 2 or 3, characterized in that: It also satisfies the following conditions: 0.02%≤Cu+Cr+Ni+Mo≤0.20%.
5. The ultra-low carbon hot-rolled steel sheet with excellent enameling performance as claimed in claim 1, 2, 3 or 4, characterized in that: Also meets: Mn / [(55 / 32) × S+(55 / 16) × O]≥1.
6. The ultra-low carbon hot-rolled steel sheet with excellent enameling performance according to any one of claims 1 to 5, characterized in that: The microstructure of the steel plate is ferrite + a small amount of cementite; the ferrite grain size level is 7 to 10; manganese oxysulfide and ferrous sulfide composite inclusions are dispersed on the ferrite, and the mass percentage of the inclusions is above 0.13%.
7. The ultra-low carbon hot-rolled steel sheet with excellent enameling performance according to any one of claims 1 to 6, characterized in that: The steel plate has a yield strength of ≥180 MPa, a tensile strength of ≥280 MPa, and an elongation of ≥38%.
8. The method for producing an ultra-low carbon hot-rolled steel sheet having excellent enameling performance according to any one of claims 1 to 7, characterized in that: The steps include: 1) Smelting, refining and continuous casting Smelting, RH or LF refining, and continuous casting into slabs according to the composition of claim 1, 2, 3, 4, or 5; 2) Hot rolling Heating temperature: 1100-1250℃, followed by hot rolling, including rough rolling and finish rolling, final rolling temperature: 800-960℃; 3) Coiling The hot-rolled steel plate is cooled by air or water and then coiled at a coiling temperature of 520 to 800°C.
Citation Information
Patent Citations
Works for enameling and enameled products
CN101517115B
Hot-rolled enamel steel plate for subway decoration, and manufacturing method thereof
CN108396236A
Steel sheet for continuous cast enameling with highly excellent unsusceptibility to fishscaling and process for producing the same
CN101356295A
Low-cost high-oxygen enamel steel produced by CSP technology and production method thereof
CN108754342A
Steel with excellent plasticity and toughness and scale explosion resistance used for glass lining and manufacturing method thereof
CN108796391A